2022
DOI: 10.1002/anie.202217798
|View full text |Cite
|
Sign up to set email alerts
|

Inside Cover: Site‐Selective Electrochemical C−H Carboxylation of Arenes with CO2 (Angew. Chem. Int. Ed. 3/2023)

Abstract: As ite-selective electrochemical … …C of arenes with CO 2 is reported by Youai Qiu and co-workers Research Article (e202214710). Ad irect metal-free,b ase-free,a nd site-selective electrochemical CÀHc arboxylation of arenes by reductive activation using CO 2 as an economic and abundant carboxyl source was developed. Ther obust nature of this strategy is reflected in abroad scope of substrates,excellent atom economy,and unique selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 0 publications
0
61
0
1
Order By: Relevance
“…16a). 60 Perylene diimide (PDI)-bridged 22 was found to complex with amino acid derivatives, resulting in a helical stacking of PDI, and the CD spectra gradually increase with the concentration of the amino acids. On the contrary, the addition of the amino acids to the solution containing 23b-23e did not immediately induce a CD signal.…”
Section: Threshold Effectmentioning
confidence: 99%
“…16a). 60 Perylene diimide (PDI)-bridged 22 was found to complex with amino acid derivatives, resulting in a helical stacking of PDI, and the CD spectra gradually increase with the concentration of the amino acids. On the contrary, the addition of the amino acids to the solution containing 23b-23e did not immediately induce a CD signal.…”
Section: Threshold Effectmentioning
confidence: 99%
“…[12,13] Nickel oxide (NiO x ) is a widely used inorganic hole-transport material in inverted PSCs due to its deep valence band (À5.4 eV), wide bandgap (>3.5 eV), suitable work function, chemical stability, optical transparency across the visible spectrum, and efficient hole collection in p-i-n PSCs. [14][15][16][17] NiO x can be synthesized using various methods, [18][19][20] including the wet chemical route. [21,22] Among these methods, chemical bath deposition (CBD) is a convenient solution route for preparing metal oxide transport layers such as SnO 2 [23,24] and NiO x .…”
Section: Introductionmentioning
confidence: 99%
“…We were still able to obtain the target product 7 in 36% yield when using phenyl selenium chloride as the reaction substrate (Scheme 3c). 1–16 These experiments showed that the reaction probably proceeds through a telluronium ion intermediate. We set out to demonstrate that the amine salt generated from amine and CO 2 may be an intermediate of this reaction.…”
mentioning
confidence: 99%
“…Organic electrosynthesis is a versatile method for establishing green and sustainable processes, 12 because dangerous and toxic oxidizers and reductants are replaced by an electric current, and the overall energy consumption is reduced. 13 Electrochemically catalyzed multicomponent reactions are green and efficient and have been used for the construction of organosulfur and organoselenium compounds. 14 However, there have been no reports to date of the synthesis of tellurium-containing heterocyclic compounds using multicomponent reactions under electrocatalysis.…”
mentioning
confidence: 99%